The rapid biophysical profile for early intrapartum fetal well-being assessment - Tongprasert F. (2014)
Objective: To determine the efficacy of the rapid biophysical profile (rBPP), which uses sound-provoked, ultrasonographically detected fetal movement and amniotic fluid index, for early intrapartum fetal well-being assessment and prediction of adverse perinatal outcomes. Methods: Rapid BPP was performed in 330 women admitted to the labor unit of Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand, from January 2005 to July 2005. Those who were delivered later than 24 h after the rBPP, or who required emergency cesarean section because of placenta previa, abruptio placentae or prolapsed cord were to be excluded. Perinatal outcomes were prospectively assessed and recorded for subsequent analysis. The predicting accuracy of rBPP was calculated according to poor outcomes, which included fetal distress, low Apgar score, admission to the neonatal intensive care unit and perinatal death. Results: Among the 330 pregnancies, there were 6 adverse perinatal outcomes (1.8%). The rBPP had a sensitivity of 50.0%, a specificity of 99.07%, a positive predictive value of 50.0%, a negative predictive value of 99.07% and an accuracy of 98.18%. Conclusion: With its simplicity, low cost and high specificity but its low sensitivity and low negative predictive value, the rBPP may be used as a back-up test to confirm fetal well-being during the early intrapartum period in developing countries. © 2006 International Federation of Gynecology and Obstetrics.